Pengembangan Bahan Ajar Morfologi Berbasis Pendekatan Komunikatif Pada Mahasiswa Jurusan Bahasa Inggris FBS UNM - Abdullah Abdullah; Asriati Asriati; Baso Jabu (Seminar Nasional LP2M UNM, 2021)
Abstrak. The problem in this research is how to develop teaching materials of Morphological learning based on a Communicative Approach to  the students of the English Department of FBS UNM, the factors that influence the implementation of materials, students worksheets, exercises and lecture program plans which are expected to improve students' knowledge and language skills. .This research is a development research that aims to develop teaching materials of morphological learning based on communicative approach to the students of the English Department of FBS UNM to improve students' knowledge and language skills, especially the English Department of FBS UNM. The development of teaching materials and learning that are planned will follow the research and development model designed by Borg & Gall (1983). This research is an extensive process in examining the needs of the students and then a product is developed specifically designed to the needs of these students in an effort to improve knowledge and language skills through morphological learning based on  communicative approach. The population of this research were students of the English Department of FBS UNM. The research sample was the students of the English Education and literature study program. The result of this research showed that there are a morphological learning material, syllabus, and design of morphologilal material of English. Kata Kunci: Learning morphological material, and communicative approach